Effectiveness of developing job performance through learning management and development in Tomasian Fast Food Corporation - Jollibee Franchise Employees - Joan B. Aguirre, Kristina A. Alipat, Gillysa Marie E. Burila, Ysabelle G. Marquez, Sharina Mikaela R. Solidor 4 0 16; 5
Introduction Human resources are significant in business operations as their performance affects the firm. Investing in human capital would benefit the company as it does not just develop its people but discover potentials that can be leveraged and utilized. Keeping employees proficient and satisfied with their jobs is essential to have an advantage over competitors. Covid-19, in recent years, caused devastation to the world and brought drastic change to economic forces such as the business industry. Companies adapt and transform to keep their business afloat despite being challenged by the pandemic. Food sector had the slowest growth in 2021. (Miraflor, 2021) The said industry almost collapsed as the government implement different quarantine orders. Learning Management and Development Programs from the past may not be effective in the current times. Effective and timely programs are prepared for employees to acquire the skills and knowledge needed for their job roles. It would be detrimental for businesses to keep their existing programs as they may not be applicable anymore. Amidst the pandemic, the learning management and development division has been trying to be resilient in thriving to flourish and prosper. Managing employee performance was a big challenge for the HR department as they must continuously provide innovative interventions to cope with the new set-up. The training and development facet is dynamic and complex. It varies depending on the needs of the employees, and it undergoes a process such as training needs analysis. Leadership style, work environment, and job satisfaction affect job performance. (Chandra & Priyono, 2016) These variables influence employee performance as it measures whether an employee is performing well. Leadership style has an impact on job performance as leaders must motivate and support employees for them to feel valued. Employees who are not motivated are the ones who underperform and undertake training. Work Environment affects employee performance. Its impact reflects through coworker support, adequate workload, employee benefits, training and development, and physical work environment. (Shammout, 2022) Job satisfaction affects job performance as it shows how an employee is committed to their work. Employees who are not satisfied with their job most likely underperform as well. According to the study by Walters & Rodriguez (2017), employee training and development help employees improve their performance. Their learnings are analyzed through KPI after receiving the program. It evaluates personal, organizational, environmental, skill level, or role perceptions factors. Factors affecting job performance should match with the intervention provided by the company. Learning management and development programs must be effective as their purpose is to improve the productivity of the employees and the company. Managerial and staff members have different kinds of training. Managers undergo leadership training, project management, risk management, etc. While basic worker training usually focuses on skill training, teamwork, self-development training, etc. It explains that providing an effective intervention to employees would enhance work performance.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2